GLAUCOMA EPIDEMIOLOGICAL SITUATION IN THE FERGANA VALLEY: REGIONAL CHALLENGES - Khoshimova D.K.; Nazarov B.M.; Qaharova D.M.; Ibrohimov T.A. (The American Journal of Medical Sciences and Pharmaceutical Research, 2024)
The aim of the research was to organize and conduct a prospective analytical epidemiological study to determine the prevalence of glaucoma in the Andijan region of the Fergana Valley.